The application of reflexivity for conservation science. (October 2021) - Beck, Jacalyn M.; Elliott, Kevin C.; Booher, Charlie R.; Renn, Kristen A.; Montgomery, Robert A.
Abstract: In recent years, conservationists have been taking an increasingly holistic, interdisciplinary approach to conservation science, utilizing many methodologies and techniques from the social sciences. Reflexivity is one social science technique that holds great potential to aid in the continued advancement of conservation science but is not yet commonly recognized or applied by conservationists. Here we establish a systems-based framework for conservation science and couple it with a discipline-specific definition of reflexivity to enable the integration of reflexivity into future conservation projects. We outline the four major tenets of reflexivity for conservation science, declaring that conservation science i ) is informed by personal values, ii ) requires true partnership, iii ) must contend with its own history, and iv ) demands progress. We present practical reflexive techniques that conservationists can use to adhere to these tenets and to foster research-informed conservation efforts that are more collaborative, resilient, and diverse. Highlights: Reflexivity is a concept based in social sciences that may help to improve conservation science but is not commonly applied. We devise a conservation-specific definition of reflexivity, list its major tenets, and describe useful reflexive techniques. Additionally, we present a systems-based framework to help conservationists re-conceptualize the complex research system. Reflexive practice has the power to support more ethical, applicable, and trustworthy conservation science.